Strategic framework improves access to stroke reperfusion across the state of Victoria Australia - Bray, Janet; Denisenko, S.; Campbell, B.; Stephenson, M.; Muller, J.; Hocking, G.; Hand, P.; Bladin, C. (Blackwell Publishing, 2017)
© 2017 Royal Australasian College of Physicians Background: In 2010, rapid access to stroke thrombolysis centres was limited in some regional areas in the Australian state of Victoria. These results, and planning for endovascular clot retrieval (ECR), have led to the implementation of strategies by the Victorian Stroke Clinical Network, the Victorian Stroke Telemedicine Program and local health services to improve state-w ide access. Aims: To examine whether access to stroke reperfusion services (thrombolysis and ECR) in regional Victoria have subsequently improved. Methods: The locations of suspected stroke patients attended by ambulance in 2015 were mapped, and drive times to the nearest reperfusion services were calculated. We then calculated the proportion of cases with transport times within: (i) 60 min to thrombolysis centres; and (ii) 180 min to two ECR centres designated to receive regional patients. Statistical comparisons to existing 2010 data were made. Results: In 2015, Ambulance Victoria attended 16 418 cases of suspected stroke (2.9% of all emergency calls), of whom 4597 (28%) were located in regional Victoria. Compared to 2010, a greater proportion of regional suspected stroke patients in 2015 were located within 60 min of a thrombolysis centre by road (77–95%, P < 0.001). A 3-h road travel time to the two ECR centres is currently possible for 88% of regional patients. Conclusion: A strategic and region-specific approach has resulted in improved access by road transport to reperfusion therapies for stroke patients across Victoria.